Tissue-specific (ts)CRISPR as an efficient strategy for in vivo screening in Drosophila - Meltzer, Hagar (Nat Commun, 2019)
Gene editing by CRISPR/Cas9 is commonly used to generate germline mutations or perform in vitro screens, but applicability for in vivo screening has so far been limited. Recently, it was shown that in Drosophila, Cas9 expression could be limited to a desired group of cells, allowing tissue-specific mutagenesis. Here, we thoroughly characterize tissue-specific (ts)CRISPR within the complex neuronal system of the Drosophila mushroom body. We report the generation of a library of gRNA-expressing plasmids and fly lines using optimized tools, which provides a valuable resource to the fly community. We demonstrate the application of our library in a large-scale in vivo screen, which reveals insights into developmental neuronal remodeling.